Jane Austen's Pride and prejudice - Firth, Colin, 1960-; Ehle, Jennifer, 1969-; Steadman, Alison, 1946-; Whitrow, Benjamin; Harker, Susannah; Bonham-Carter, Crispin; Chancellor, Anna.; Sawalha, Julia, 1968-; Bamber, David; Langton, Simon; Austen, Jane, 1775-1817.; Arts and Entertainment Network; et al. ([London?] : British Broadcasting Corp., 2001)
The story of lively and rebellious Elizabeth, one of five unmarried daughters living in the countryside of 19th century England, in a world where an advantageous marriage is a woman's sole occupation.
Originally produced for 1995 miniseries television broadcast.
Booklet (7 p.) includes list of chapters, and cast and crew reminiscences.
Special features: vol. 1: biographies ; vol. 2: featurette (The making of Pride and prejudice).
Based on the novel by Jane Austen.
Film format: anamorphic widescreen (2.35:1).
Photography, John Kenway ; film editor, Peter Coulson ; music, Carl Davis.
Keywords: Austen, Jane, -- 1775-1817 -- Film and video adaptations; Young women -- England -- Drama; Courtship -- England -- Drama; Television adaptations; Television mini-series.; Video recordings for hard of hearing people; England -- Social life and customs -- 19th century -- Drama; Love stories